Structures for caribou management and their status in the circumpolar north - Klein, D.R. (Rangifer, 1996)
Large herds of caribou (Rangifer tarandus) in Canada, Alaska, and Russia that winter in northern coniferous forests and summer in tundra of the Arctic have provided a sustainable source of meat and other products for indigenous peoples for thousands of years. Several different administrative structures for management of large caribou herds have emerged throughout the circumpolar North. In Russia under the previous Soviet government, the herd of the Taimyr Region, numbering around 500 000 caribou, was managed under a harvest quota system for both subsistence use by indigenous people and commercial sale of meat and skins. In North America, as indigenous peoples have gained increasing political empowerment, systems for caribou management have been undergoing change. Establishment of the Beverly and Qamanirjuaq Caribou Management Board in Canada, with majority representation from users of the resource, provides a model and a test of the effectiveness of a comanagement system. The Western Arctic Herd in northwestern Alaska, numbering close to 500 000 caribou, has been managed under the traditional American system of game management, with user advisory groups, but with management decisions resting with a statewide Board of Game, whose major representation is from sport-hunting interests. The Porcupine Caribou Herd, which is shared by the United States and Canada, is the focus of an international agreement, in principle designed to assure its continued productivity and well-being. The diversity of systems for caribou management in the circumpolar North provides an opportunity for comparing their effectiveness.